A multicentre roadmap to restart elective cardiac surgery after COVID‐19 peak in an Italian epicenter. Issue 9 (25th June 2021) - Rosati, Fabrizio; Muneretto, Claudio; Baudo, Massimo; D'Ancona, Giuseppe; Bichi, Samuele; Merlo, Maurizio; Cuko, Besart; Gerometta, Piersilvio; Grazioli, Valentina; Giroletti, Laura; Di Bacco, Lorenzo; Repossini, Alberto; et al.
Abstract: Background: During the Italian Phase‐2 of the coronavirus pandemic, it was possible to restart elective surgeries. Because hospitals were still burdened with coronavirus disease 2019 (COVID‐19) patients, it was focal to design a separate "clean path" for the surgical candidates and determine the possible effects of major surgery on previously infected patients. Methods: From May to July 2020 (postpandemic peak), 259 consecutive patients were scheduled for elective cardiac surgery in three different centers. Our original roadmap with four screening steps included: a short item questionnaire (STEP‐1), nasopharyngeal swab (NP) (STEP‐2), computed tomography (CT)‐scan using COVID‐19 reporting and data system (CO‐RADS) scoring (STEP‐3), and final NP swab before discharge (STEP‐4). Results: Two patients (0.8%) resulted positive at STEP‐2: one patient was discharged home for quarantine, the other performed a CT‐scan (CO‐RADS: <2), and underwent surgery for unstable angina. Chest‐CT was positive in 6.3% (15/237) with mean CO‐RADS of 2.93 ± 0.8. Mild‐moderate lung inflammation (CO‐RADS: 2–4) did not delay surgery. Perioperative mortality was 1.15% (3/259), and cumulative incidence of pulmonary complications was 14.6%. At multivariable analysis, only age and cardiopulmonary bypass (CPB) time were independently related to pulmonary complications composite outcome (age >75 years: odds ratio [OR]: 2.6; 95% confidence interval [CI]: 1.25–5.57; p = 0.011; CPB >90 min. OR: 4.3; 95% CI: 1.84–10.16; p = 0.001). At 30 days, no periprocedural contagion and rehospitalization for COVID‐19 infections were reported. Conclusions: Our structured roadmap supports the safe restarting of an elective cardiac surgery list after a peak of a still ongoing COVID‐19 pandemic in an epicenter area. Mild to moderate CT residuals of coronavirus pneumonia do not justify elective cardiac surgery procrastination.